Simultaneous Synthesis of Partially Homologous Oligonucleotide Sequences - Philip Hendry (BioTechniques, 1998)
A technique is described that allows the concurrent synthesis of homologous regions of separate oligonucleotides. The technique utilizes synthesis columns that are readily interconverted between single-chambered and dual-chambered. The regions of the oligonucleotides that differ are synthesized separately with single-chamber columns, and with the single modules joined, the homologous regions synthesized simultaneously. After synthesis, the chambers are opened separately, the solid-phase-bound oligonucleotides are placed in deprotection vials and treated as normal. Compared with standard syntheses, no decrease in yield or oligonucleotide quality was observed. This technique can result in significant savings in time and reagent costs when synthesizing a series of homologous oligonucleotides. This technique could be extended to the simultaneous synthesis of more than two oligonucleotides, possibly up to four or five oligonucleotides in an appropriate multichambered column.